The corpus-driven revolution in Polish Sign Language: the interview with Dr. Paweł Rutkowski - Iztok Kosem; Victoria Nyst (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
Dr. Paweł Rutkowski is head of the Section for Sign Linguistics at the University of Warsaw. He is a general linguist and a specialist in the field of syntax of natural languages, carrying out research on Polish Sign Language (polski język migowy — PJM). He has been awarded a number of prizes, grants and scholarships by such institutions as the Foundation for Polish Science, Polish Ministry of Science and Higher Education, National Science Centre, Poland, Polish–U.S. Fulbright Commission, Kosciuszko Foundation and DAAD. Dr. Rutkowski leads the team developing the Corpus of Polish Sign Language and the Corpus-based Dictionary of Polish Sign Language, the first dictionary of this language prepared in compliance with modern lexicographical standards. The dictionary is an open-access publication, available freely at the following address: www.slownikpjm.uw.edu.pl/en/.